Putative muscle stem cells promote Xenopus tail regeneration by modifying macrophage function via c1qtnf3 - Sumika Kato; Takeo Kubo; Taro Fukazawa (Proceedings of the National Academy of Sciences, 2025)
In Xenopus laevis tadpole tail regeneration, lineage-restricted tissue stem cells produce differentiated cells that form regenerated tail tissues, but the behavioral dynamics of tissue stem cells during tail regeneration remain largely unknown. We previously reported that multiple tissue stem/progenitor cells can be efficiently enriched from regeneration buds using the side population (SP) method. Here, we performed trajectory inference using single-cell RNA sequencing data of the SP fraction to construct differentiation trajectories and identify putative tissue stem cell populations that initiate differentiation pathways. We found that complement c1q tumor necrosis factor-related protein 3 ( c1qtnf3 ) is specifically expressed in putative muscle stem cells (MSC) and, using knockdown (KD; CRISPR/Cas9-based F0 crispants) experiments, demonstrated that c1qtnf3 is necessary for tail regeneration. Furthermore, we found that the impaired tail regeneration by c1qtnf3 KD was accompanied by abrogation of macrophage-like cell accumulation at the amputation site. These phenotypes were rescued by macrophage-like cell-specific forced expression of neutrophil cytosolic factor 1 , a gene related to effector molecule production in myeloid cells, suggesting that the impaired tail regeneration by c1qtnf3 KD is due to macrophage dysregulation. Our findings suggest that, in Xenopus , putative MSC modulate macrophage function via c1qtnf3 expression for successful tail regeneration.